Shared decision-making in type 2 diabetes: a systematic review of patients’ preferences and healthcare providers’ perspectives - Maryam Peimani; Anita L. Stewart; Gholamreza Garmaroudi; Ensieh Nasli-Esfahani (BMC Health Services Research)
Abstract Background Shared decision-making (SDM) is crucial for type 2 diabetes mellitus (T2DM) management due to the complexity of treatment options. This systematic review sought to understand T2DM patients’ preferences and diabetes care providers’ perspectives regarding SDM, and the barriers and facilitators to SDM. Methods Five databases were searched from 2000 to 2023 (Medline/PubMed, Web of Science, Scopus, PsycINFO, and Embase). All included papers were quantitative and qualitative studies regarding preferences of patients with T2DM for SDM, perspectives of providers on SDM, and their barriers and facilitators to SDM. Quantitative findings were extracted as percentages, and qualitative findings were extracted as presented in the original research paper. Study selection was carried out independently by two authors, with discrepancies resolved by consensus and by consultation with the supervisor. The Joanna Briggs Institute Checklist for Qualitative Research and for Cross Sectional Studies was used to evaluate the risk of bias of included papers. Results Thirty-four studies were included in this review; 22 focused on T2DM patients' decision-making preferences, 7 focused on perspectives of diabetes care providers, and 5 addressed both. Of the 27 studies of T2DM patients, 20 (ten quantitative and ten qualitative studies) reported that respondents preferred and valued SDM and wanted to make decisions in collaboration with a provider. Of the 12 studies of providers, only 5 reported that providers had positive views towards SDM and preferred to involve patients in decision-making. A comprehensive list of SDM facilitators and barriers included patient factors (facilitators like higher health literacy and motivation, and barriers like blind trust in physicians and poor health), provider factors (facilitators like a physician's information-giving behavior and medical knowledge/technical skills, and barriers like a paternalistic attitude and poor interpersonal style), and context factors (facilitators like physician accessibility and availability, and barriers like a lack of system support and low continuity). Conclusion Although SDM is important for most patients living with diabetes, the evidence from included studies suggest that providers in diabetes practice do not universally express positive views towards SDM. Because T2DM patients and their providers need to work together to implement the SDM approach satisfactorily, there is a need to encourage more providers to do so.